Rola systemów filozoficzno-religijnych w państwie i prawie japońskim po 1945 r. - Anna Chodorowska (In Gremium. Studies in History, Culture and Politics, 2015)
The role of philosophical and religious systems in japanese state and law after 1945The author undertakes to discuss the relationship between the state and religion in Japanese law. This article aims to show the relation at the level of the state, law and religion. The latter is understood very broadly, in the context of the state in Japan, as a belief and a philosophy of life. At the same time the author looks at religion (belief ) through the Japanese legislations, especially the Constitution of Japan of 11 Mars 1946, so called Showa Constitution and the existing legal regulations.Firstly, the article aims to explain the concept of religion and philosophy in Japan. Since it is difficult to clearly separate the philosophy from religion in the history of traditional Japanese thought. The concept of religion is identified with the philosophy of life. Showing the ‘Japanese’ understandingof the concept of philosophy as a metaphysical worldview, which is grounded in cultural values. The author presents the historical development of religion, belief and philosophical thoughts in Japan (including Shinto, Confucianism, Buddhism, folk beliefs, so-called Shinko shukyo and Christianity). This article attempts to discuss the impact of the religion, beliefs and different  philosophical systems and thinking, which influenced the formation of the Japanese state, including the evolution of phenomena characteristic of Japanese culture. The article presents the development of religious and philosophical thought in Japan, in their historical context, and their impact on the social and political life of the country of the Rising Sun (e.g. the fundamental values of Japanese culture such as the cult of the emperor and the attitude of Japanese to the state, to the power and to the law). The article shows the relations between the state-religion (belief) in the history and law of Japan, both in the Meiji Constitution, and in the current Showa Constitution (including the role of religion in the Meiji period and its influence on the formation of the modern Japanese state). The article presents the relation between law, religion and state in the context of the constitutional regulations relating to the freedom of religion and conscience (i.e. the issues of guarantees of religious freedom and their actual preservation).